Symmetry-dependent carrier relaxation dynamics and charge–density–wave transition in DyTe3 probed by polarized femtosecond spectroscopy. (31st July 2015) - Tsuchiya, S; Sugawara, Y; Tanda, S; Toda, Y
Abstract: Photo-induced quasi-particle (QP) relaxation dynamics with different symmetries have been investigated for the multiple charge–density–wave (CDW) compound DyTe3 by using ultrafast polarized pump-probe spectroscopy. By performing symmetry analysis, the QP dynamics with isotropic A1g and anisotropic B2g symmetry were found to show unique anomalies at the first and second CDW transitions. Both the temperature dependence and pump fluence dependence indicate that the B2g response is very sensitive to the underlying lattice deformation, which provides critical insight into the multiple CDW formations.